Detection of SARS‐CoV‐2 virus in middle ear effusions and its association with otitis media with effusion - Fu, Xiao; Wang, Zhujian; Chen, Binjun; Sun, Haojie; Lyu, Jihan; Shao, Jing; Lu, Xiaoling; Xu, Jianghong; Yang, Juanmei; Chi, Fanglu; Huang, Yibo; Ren, Dongdong (Journal of medical virology, 2024)
A large‐scale outbreak of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS‐CoV‐2) occurred in Shanghai, China, in early December 2022. To study the incidence and characteristics of otitis media with effusion (OME) complicating SARS‐CoV‐2, we collected 267 middle ear effusion (MEE) samples and 172 nasopharyngeal (NP) swabs from patients. The SARS‐CoV‐2 virus was detected by RT‐PCR targeting. The SARS‐CoV‐2 virus, angiotensin‐converting enzyme 2 (ACE2), and transmembrane serine protease 2 (TMPRSS2) expression in human samples was examined via immunofluorescence. During the COVID‐19 epidemic in 2022, the incidence of OME (3%) significantly increased compared to the same period from 2020 to 2022. Ear symptoms in patients with SARS‐CoV‐2 complicated by OME generally appeared late, even after a negative NP swab, an average of 9.33 ± 6.272 days after COVID‐19 infection. The SARS‐CoV‐2 virus was detected in MEE, which had a higher viral load than NP swabs. The insertion rate of tympanostomy tubes was not significantly higher than in OME patients in 2019–2022. Virus migration led to high viral loads in MEE despite negative NP swabs, indicating that OME lagged behind respiratory infections but had a favorable prognosis. Furthermore, middle ear tissue from adult humans coexpressed the ACE2 receptor for the SARS‐CoV‐2 virus and the TMPRSS2 cofactors required for virus entry.